A POSSIBLE MODEL FOR INITIATION OF ULF OSCILLATION IN MAGMA - Kopytenko Y.A.; Nikitina L.V. (My University, 2004)
During the period just prior to an earthquake, an electomagnetic emission develops over seismic zones. In this paper, a model of excitation of magnetic fields over zones of volcanic activity is proposed. Movement of magma along volcanic channels precedes an earthquake, hydrodynamic processes in the moving magma can lead to formation of waves and vortices in the flow which, in turn, can cause development of magnetic fields in conducting magma. During this period, the movement of the magma intensifies leading to a corresponding intensification of the magnetic fields. In this paper, different possible sources of ULF pulsation in magma are examined,and the variable geomagnetic fields induced by this pulsation are estimated.